Factors affecting onychomycosis in patients with psoriasis - Bozdemir, Neslihan Yuksel; Yuksel, Esma Inan; Toraman, Zulal Asci; Cicek, Demet; Demir, Betul; Gunbey, Fatma (Wiley, 2022)
Prevalence of onychomycosis increases in patients with psoriasis and that psoriasis predisposes to onychomycosis. It was aimed to determine the frequency of onychomycosis and responsible pathogens in patients with psoriasis, to reveal their differences compared to the population without psoriasis, and to determine the factors in this study. The study included 81 patients with nail disorder diagnosed with psoriasis. Clinical findings, psoriasis area and severity index (PASI), nail psoriasis severity index (NAPSI) scores, body mass indexes (BMI) and laboratory characteristics were recorded. Mycological examination by direct microscopy and fungal culture was performed both on nails that were considered onychomycosis and on nails with any of the psoriatic nail findings. The prevalence of onychomycosis was 27.2% in psoriasis patients. Nail involvement of psoriasis was found in 31.3% of the patients using biologic agents, 5.9% of those receiving conventional treatment, and 31.3% of those receiving topical treatment and 68.8% of the patients who did not receive treatment at all. The difference between the patients who did not receive treatment and those who received conventional treatment was significant (p < 0.05). There was growth in the fungal culture in 23.5% of the patients with psoriasis. There was no statistically significant relationship between onychomycosis and PASI, NAPSI score, and BMI (p > 0.05). Since the prevalence of onychomycosis in psoriasis patients receiving conventional and anti-TNF-alpha therapy is higher than in patients not receiving treatment, nail changes in these patients should be evaluated in more detail for the presence of onychomycosis. In addition, since more than one fungal agent can grow and non-dermatophyte molds are seen more frequently in patients with psoriasis, it should be taken into account that native and fungal culture examinations should be performed together.
Keywords: biological therapy; nail psoriasis; onychomycosis; psoriasis; psoriasis treatment